Financial Feasibility Analysis of Crab (Portunus pelagicus) Fishing Business in Pasir Limau Kapas District, Rokan Hilir Regency - Zulhami, M; Arief, Hazmi; Yolandika, Clara (Jurnal Perikanan dan Kelautan, 2025)
Pasir Limau Kapas District is a coastal area in Rokan Hilir Regency, known for its unique character as a center for traditional fishing. Crab production in this District in 2018 was recorded at 486 tons, then increased to 512 tons in 2019, and 527 tons in 2020. In 2021, there was a slight decrease to 498 tons due to extreme weather that affected fishing strength, but it increased again to 538 tons in 2022. This study was conducted in February 2025 at Pasir Limau Kapas District, Rokan Hilir Regency, aiming to calculate the investment, total costs, income, and profits, and to analyze the financial feasibility of the crab fishing business. The method used in this study was a survey method with a total of 35 crab fishermen as respondents. The study results indicated that the average investment spent by fishermen was IDR 17,430,722.69. Total costs are IDR 92,105,356.14/year, revenue is IDR 104,996,571.43/year, and profit is IDR 12,891,215.29/year. The chopped crab fishing business demonstrates good economic feasibility. With an R/C Ratio of 1.14, this business generates revenues greater than the costs incurred. The return on investment (ROI) of 14% indicates that this business provides moderate profits compared to the total costs incurred. The payback period (PPC) of 1.35 years, or approximately 1 year and 4 months, is relatively fast, allowing fishermen to recover their initial investment relatively quickly. Although it does not generate significant profits, this business can be a sustainable source of livelihood for fishermen because it meets the required business feasibility parameters.